2015
DOI: 10.1002/pros.22955
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adenosine receptor subclasses in malignant and adjacent normal human prostate tissues

Abstract: These results indicated for the first time, the differential mRNA expression profile and protein levels of adenosine receptors in the human prostate cancer. Interestingly, the A2B adenosine receptor followed by A3 is highly expressed in prostate tumor samples in comparison with the adjacent normal tissues. The findings support the possible key role of A2B adenosine receptor in promoting cancer cell growth and suggest that A2B may be a novel target for prostate cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…It has been documented that the expression level of A2bR was the highest among the four adenosine receptor subtypes in different ovarian and prostate cancer cell lines [ 9 , 13 ]. Similarly, compared to the adjacent normal tissues, the mean expression of A2bR was increased in diverse human cancers, including ovarian, lung, liver, oral, colon and prostate cancers [ 9 , 10 , 14 17 ]. In addition, high A2bR expression in triple negative breast cancer was significantly associated with poor prognosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that the expression level of A2bR was the highest among the four adenosine receptor subtypes in different ovarian and prostate cancer cell lines [ 9 , 13 ]. Similarly, compared to the adjacent normal tissues, the mean expression of A2bR was increased in diverse human cancers, including ovarian, lung, liver, oral, colon and prostate cancers [ 9 , 10 , 14 17 ]. In addition, high A2bR expression in triple negative breast cancer was significantly associated with poor prognosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine acts its biological functions via four subtypes of adenosine receptors (ARs), A1, A2a, A2b, and A3 [ 8 ]. Recently, studies indicated that A2b receptor (A2bR) was highly expressed in various tumors due to the hypoxic environments of solid tumors [ 9 , 10 ]. Suppression of A2bR expression with shRNA was observed to significantly inhibit cell proliferation in oral cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…45 The latter would be present at higher levels in prostate cancer tissues than in control ones; one of them, the A 2B , was reported to specifically promote prostate cancer cell growth. 44 This pathway therefore can be proposed as a novel target for prostate cancer treatment and represents a possible mechanism to explain the protective role of caffeine in the present study.…”
Section: Cancer Epidemiologymentioning
confidence: 66%
“…A 2B AR expression at both the mRNA and protein level is higher in malignant prostate cancer tissue from human patients when compared with normal control prostate tissue (Mousavi et al, 2015). In addition, the A 2B AR has been implicated in cell proliferation and angiogenesis, accounting for its apparent role in the pathogenesis of a number of solid tumors (Li et al, 2005;Ryzhov et al, 2008;Ma et al, 2010;Cekic et al, 2012;Iannone et al, 2013;Wei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The A 2B AR is a pleiotropically coupled GPCR, signaling via both G s and G q proteins (Linden et al, 1999;Fredholm et al, 2001a), and represents a key example of a highly dynamic GPCR whose expression is modified by disease. The A 2B AR is significantly upregulated by HIF-1a in a number of cancers (Li et al, 2005), including human prostate cancer (Wei et al, 2013;Mousavi et al, 2015). Until recently, the A 2B AR was presumed to have minor physiologic significance, in part due to its relatively low affinity for the endogenous agonist adenosine (Feoktistov and Biaggioni, 1997;Fredholm et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%